Prospective Longitudinal Patient-Reported Satisfaction and Health-Related Quality of Life following DIEP Flap Breast Reconstruction: Effects of Reconstruction Timing. Issue 5 (2nd March 2022) - Ochoa, Oscar; Garza, Ramon; Pisano, Steven; Chrysopoulo, Minas; Ledoux, Peter; Arishita, Gary; Ketchum, Norma; Michalek, Joel E.; Nastala, Chet
Abstract : Background: Without reconstruction, mastectomy alone can produce significant detrimental effects on health-related quality of life. The magnitude of quality-of-life benefits following breast reconstruction may be unique based on timing of reconstruction. Facilitated by the BREAST-Q questionnaire, characterization of how reconstruction timing differentially affects patient-reported quality of life is essential for improved evidence-based clinical practice. Methods: Consecutive DIEP flap breast reconstruction patients prospectively completed BREAST-Q questionnaires preoperatively and at two different time intervals postoperatively. The first (postoperative time point A) and second (postoperative time point B) postoperative questionnaires were completed 1 month postoperatively and following breast revision/symmetry procedures, respectively. Postoperative flap and donor-site complications were recorded prospectively. Stratified by timing (immediate versus delayed) of reconstruction, preoperative clinical data, operative morbidity, and BREAST-Q scores were compared at all time points. Results: Between July of 2012 and August of 2016, 73 patients underwent 130 DIEP flap breast reconstructions. Collectively, breast satisfaction, psychosocial well-being, and sexual well-being scores significantly ( p < 0.001) increased postoperatively versus baseline. Chest and abdominal physical well-being scores returned to baseline levels by postoperative time point B. Preoperatively, patients undergoing delayed breast reconstruction reported significantly ( p < 0.05) lower breast satisfaction, psychosocial well-being, and sexual well-being scores compared to immediate reconstruction patients. Postoperatively, delayed and immediate reconstruction patients reported similar quality-of-life scores. Outcome satisfaction and flap and donor-site morbidity were similar between groups irrespective of timing of reconstruction. Conclusions: In this prospective study, patient-reported outcomes demonstrate significant improvements in breast satisfaction, psychosocial well-being, and sexual well-being among patients following DIEP flap reconstruction. Moreover, preoperative differences in quality-of-life scores among delayed/immediate reconstruction patients were eliminated postoperatively. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.